Shrimp health assessment in the west coast of Peninsular Malaysia with emphasis on the impact of aquaculture activity - Mohamed Fouzi, Mohamed Naleem (2009)
Rapid growth of shrimp farming has caused destruction of mangroves, pollution of coastal waters due to nutrient loading, reduced biodiversity of wild shrimp and increased disease occurrence. The present study was undertaken to assess biodiversity of wild shrimp and prevalence of shrimp virus in disturbed mangrove and pristine areas. The study also quantified stress in Penaeus monodon exposed to ammonia, and their subsequent susceptibility to white spot syndrome virus (WSSV). Coastal waters off Matang and Kuala Selangor were selected as pristine and disturbed mangrove areas respectively for monthly sampling of shrimp and water from March 2006 to February 2007. Shrimp were sampled for the first 6 months during high tide by trawling and for the following 6 months during low tide by cast net. Penaeus monodon were challenged by WSSV following the exposure of different levels (B.1, 3.B and 1.1 mg/L) of total ammonia nitrogen (TAN), Haemo-chemicals [alanine transaminase (ALT), aspartate transaminase, (AST), total protein (TP), glucose and electrolytes (Na+, cI, and K+)] were measured to quantify the stress caused by ammonia and WSSV. TaqManbased real-time PCR was used to relatively quantify WSSV load in the shrimp exposed to different levels of TAN with positive control shrimp which were not exposed to TAN, but challenged with WSSV. A total of 11,099 shrimp belonging to 12 penaeids and two palaemonids species were collected over 12 months from both sites. Mean number of species (7.44 ± 0.35), density (0.7B±O.1 shrimp/m2) and Shannon-Wiener diversity index (1.4±0.1) of shrimp caught in the coastal waters off Matang were significantly higher (p-c 0.01) than that off Kuala Selangor (6.29±O.35, 0.49±O.07 shrimp/m2 and 1.1±0.1 respectively). Nutrients (TAN, total nitrogen, and total phosphorous) and chlorophyll a were significantly higher in the coastal waters off Kuala Selangor than that off Matang. Prevalence of WSSV in Kuala Selangor which was significantly correlated with TAN (~ = 0.B26, p<0.01) and nitrite (~ = 0.962, p<0.01) was 5.1% in seven shrimp species, including Macrobrachium equidense, Macrobrachium rosenbergii, Parapenaeopsis hardwickii, and Metapenaeus affinis caught in the wild. In the coastal ecosystem of Kuala Selangor, the destruction of mangroves and elevated nutrient loadings due to shrimp farming activity might have diminished the biodiversity of shrimp. Furthermore, escapees of shrimp and other aquatic organisms from adjacent shrimp ponds might have been the source of infection to the wild shrimp population, where the infection would probably be predisposed by the elevated nutrients (TAN). The shrimp exposed to 8.1 mg/L TAN for 10 days revealed significantly high haemolymph ALT, AST and TP, while shrimp exposed to 3.8 mg/L TAN showed significantly low TP. These changes in haemolymph parameters showed that exposure to 3.8 mg/L TAN for 48 hrs was sufficient to stress the shrimp. Stress in shrimp exposed to ammonia for 10 days further increased significantly when shrimp were challenged to WSSV. In addition, TP in shrimp exposed to 1.1 mg/L, 3.8 mg/L and 8.1 mg/L TAN decreased with increase in TAN treatments. There was significantly higher virus load in shrimp exposed to three different concentrations of TAN in the same ascending order as for the haemo-chemical parameters. Even at low concentration (1.1 mg/L TAN) ammonia stress can increase shrimp susceptibility to infection as shown by fold difference of WSSV load. Therefore, exposure of shrimp to ammonia increases their susceptibility to WSSV by decreasing the immuno competence as illustrated by haemochemical parameters.